2019
DOI: 10.1177/0379572119848287
|View full text |Cite
|
Sign up to set email alerts
|

Global Patterns of Adolescent Fruit, Vegetable, Carbonated Soft Drink, and Fast-Food Consumption: A Meta-Analysis of Global School-Based Student Health Surveys

Abstract: Background: Adolescence presents an opportunity to influence diet, which impacts present and future health outcomes, yet adolescent diets globally are poorly understood. Objective: We generate evidence on adolescent diets globally and explore patterns and trends by subpopulation. Methods: We estimated mean frequency of consumption and prevalence of less-than-daily fruit and vegetable consumption, at-least-daily carbonated beverage consumption, and at-least-weekly fast-food consumption among school-going adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
81
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(94 citation statements)
references
References 41 publications
9
81
1
3
Order By: Relevance
“…The overall prevalence of fast-food consumption for at least 1 day per week found in our study was much higher than that reported in the literature (55.2% vs. 49.1%) [5,12]. Only adolescents with complete data on height, weight, and fast-food consumption were included in our study, therefore the prevalence obtained in our study may be more realistic and reliable.…”
Section: Discussioncontrasting
confidence: 43%
See 4 more Smart Citations
“…The overall prevalence of fast-food consumption for at least 1 day per week found in our study was much higher than that reported in the literature (55.2% vs. 49.1%) [5,12]. Only adolescents with complete data on height, weight, and fast-food consumption were included in our study, therefore the prevalence obtained in our study may be more realistic and reliable.…”
Section: Discussioncontrasting
confidence: 43%
“…All of these findings indicate that the confounding factors, such as SES, should be considered in the analysis between obesity and fast food consumption. Unhealthy eating patterns formed in adolescence have lasting effects on future health [12]. Considering the popularity of fast food among young adolescents in LMICs, there is an urgent need for policies, strategies, and recommendations to develop a healthy dietary environment in these countries.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations